A sample survey of farming types in the divisions of Albany and Bathurst - Davies, R J (Rhodes University, Faculty of Science, Department of Geography, 1955)
[From Introduction]. It is the purpose of this thesis to examine some of the broad relationships which exist between different land use types and farming practises on the one hand and the geographical environment on the other. The enquiry is confined to the study of a number of farm units which have been selected within the area enclosed by the District of Albany and Bathurst situated in the south-East coastal belt of the Cape Province. The procedure adapted conforms broadly to that of a project carried out in South America by R.S. Platt of the University of Chicago and embodied in hls book "Latin America, Countryside and United Regions." Platt's project, he notes, consists of a collection of "small field studies in a frame of complex generalisations." It does not aim to give a complete geographical account of the regions he selected for investigation, but is an attempt to enlarge geograpical understanding of the respective areas.
Keywords: Agriculture -- South Africa -- Eastern Cape